2018
DOI: 10.3390/su10072198
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Longevity and Sustainable Development in a Family Farming System

Abstract: This paper focuses on small holding, family farming in Southeast Spain where agricultural economic activity is predominantly organized around cooperative business models. A variety of diverse studies on the Almería agricultural and credit cooperative sector and the exploration of social-economic and eco-social indicators, in addition to economic-market indicators are presented. Each correspond to a cooperative "logic" that spans theoretical perspectives from the dominant economic-market model, new institutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
(43 reference statements)
0
22
0
3
Order By: Relevance
“…For example, because farmers are often older and less educated, cooperatives can establish outreach activities to visit farms and provide them with relevant information. One example of a successful model includes the Almería Agricultural Cooperatives in Southwest Spain [32]. These cooperatives function as a market and non-market coordination mechanism for both individuals and local institutions, such as contributing to knowledge systems related to farm labor and employing agricultural technicians to reduce the usage of pesticides [32].…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, because farmers are often older and less educated, cooperatives can establish outreach activities to visit farms and provide them with relevant information. One example of a successful model includes the Almería Agricultural Cooperatives in Southwest Spain [32]. These cooperatives function as a market and non-market coordination mechanism for both individuals and local institutions, such as contributing to knowledge systems related to farm labor and employing agricultural technicians to reduce the usage of pesticides [32].…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…One example of a successful model includes the Almería Agricultural Cooperatives in Southwest Spain [32]. These cooperatives function as a market and non-market coordination mechanism for both individuals and local institutions, such as contributing to knowledge systems related to farm labor and employing agricultural technicians to reduce the usage of pesticides [32]. Similarly, many food certifications also require environmentally friendly production practices, such as organic farming.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Giagnocavo et al focus on cooperatives active in the fruit and vegetable industry of Almeria, Spain [10]. They review a number of studies on these organizations and conclude that the longevity and survival of these organizations are linked to their ability to constantly adapt to industry crises and challenges.…”
Section: Emerging Themes and Insights From The Special Issuementioning
confidence: 99%
“…EC (2019b); Chlebicka and Pietrzak (2018). Giagnocavo et al (2018) showed that companies with a cooperative structure for marketing, financing, processing and other collective services, are an effective organizational coordination mechanism for small-scale farmers. They found longevity and high ability of the cooperatives, relying on collective collaboration, to meet the needs and challenges of both members and the community.…”
Section: Discussionmentioning
confidence: 99%